THE TWO-STREAM MULTI-HARMONIC FEL AS A POWERFUL SOURCE OF FEMTO-SECOND WAVE PACKAGES - Kulish, V.V.; Lysenko, A.V.; Mayornikov, I.G. (Proceedings of National Aviation University (archive), 2005)
A possibility to construct a powerful source of femto-second wave packages is analyzed. The method as well as design variant of the system for forming such packages (the multi-harmonic two-stream superheterodyne free electron laser - MTSFEL) are proposed. It is shown that very short packages (units– tens femto-second) can be obtained in the case, when the frequency of the input monochromatic (transforming) signal is much less than the optimal frequency for two-stream instability.